REZIM SEKSUALITAS DAN AGAMA SKETSA POLITIK TUBUH PEREMPUAN DALAM ISLAM - Sundari, Akhiriyati (LPPM IAIN Parepare, 2017)
This paper examines the various issues of sexuality in Islamic discourse. The discussion in this study attempts to examine the discourse of female sexuality at the beginning of Prophet's prophethood and then evolves over the development of the age to give birth to various inequalities and injustices against women in the sexual realm. There are at least three issues concerning sexual injustice in women; first, the Islamic tradition in the post-Prophetical Jurisprudence which places women as 'male sexual needs ministers' and 'sexual generations'. Second, the tendency of female body consumerism in modern industrial civilization. Third, local traditions in certain cultures still attach stereotypes to women as 'passengers' of male social glory.